POLITENESS IN THE STATE COURT OF PALEMBANG - Wahidy, Achmad; Emzir, Emzir; Rasyid, Yumna (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This study aims to describe and gain an in-depth understanding of politness in state court in Palembang Class 1A. The focus of the research is the ploitness of the participants in the trial with researchof politeness in terms of cultural aspects in state court in Palembang Class 1A. Palembang South Sumatra Province. This research is a qualitative research with ethnography method of communication. Data collection techniques and procedures used are observation, recording and transcripts, and interviews. To verify the validity of data, carried out with credibility, transferbility, dependebility, and comfirmability. Data analysis was done by transcribing the recorded data into written form, then analyzed by focus and research. Based on data analysis, politeness state court in Palembang Class 1A Palembang descriptively expressed through cultural aspects in the form of verbal communication include the use of voice (accent) and the use of greeting forms in the communication session and non-verbal communication including kinesics such as nods and head shake and eyes contact, and kinesthetics in the form of a handshake performed by participants when communication takes place in the trial.